PENGGUNAAN MULTIMEDIA DALAM SISTEM PEMBELAJARAN PROGRAM STUDI PENDIDIKAN FISIKA DI UNIVERSITAS PASIR PENGARAIAN - Hatika, Rindi Genesa (Edu Research, 2015)
Learning physics is supposed that a difficult subject, most of the students whohad studied physics only understand the formula physics, without comprehending the basic concepts that’s implied in physics itself. Therefore, the objectives of the study was to find out the learning outcomes if the student taught physics by using ofmultimedia in physics education program, the University of Pasir Pengaraian. The research designed was a pre experiment ; the One Shot Case Study. The sample of the research was the fourth semester students of physical education program who tookcourses in introductory physics core